2012
DOI: 10.1021/ja305573g
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Single Metal Nanoparticle Collisions by Open Circuit (Mixed) Potential Changes at an Ultramicroelectrode

Abstract: Single nanoparticle (NP) collisions were successfully observed by a potentiometric measurement. The open circuit potential (OCP) of a measuring Au ultramicroelectrode (UME) changes when Pt NPs collide with the UME in a hydrazine solution. The OCP change is related to the redox processes, the concentration of particles, particle size, and electrode size. Compared with the amperometric technique, this approach has several advantages: higher sensitivity, simpler apparatus, fewer problems with NP decomposition, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
141
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(146 citation statements)
references
References 18 publications
(27 reference statements)
4
141
0
1
Order By: Relevance
“…Bard and co-workers previously reported the observation of a spike-shaped i−t response in the case of water oxidation with IrO x NPs at a Au UME and suggested that the NP bounces off the electrode rather than remaining stuck on the electrode surface. 10 Assuming that the sharp current spikes due to proton reduction with citrate-capped Pt NPs at Hg/Pt UME are due to electrostatic repulsion and are not specific to Hg, one would expect to observe a similar i−t response under similar conditions with a different electrode material such as Bi. To test this hypothesis, proton reduction experiments were performed at Bi/Pt UMEs with the same citrate-capped Pt NPs.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Bard and co-workers previously reported the observation of a spike-shaped i−t response in the case of water oxidation with IrO x NPs at a Au UME and suggested that the NP bounces off the electrode rather than remaining stuck on the electrode surface. 10 Assuming that the sharp current spikes due to proton reduction with citrate-capped Pt NPs at Hg/Pt UME are due to electrostatic repulsion and are not specific to Hg, one would expect to observe a similar i−t response under similar conditions with a different electrode material such as Bi. To test this hypothesis, proton reduction experiments were performed at Bi/Pt UMEs with the same citrate-capped Pt NPs.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Experiments typically employ a Faradaically-inactive electrode that is exposed to a solution, which contains freely-diffusing nanoparticles. [4][5][6][7][8][9] Due to the nanoparticles' random Brownian motion, particles then stochastically impact on the biased electrode and briey adopt the electrode potential while they are located within tunnelling distance to the electrode. During the moment of impact, nanoparticles may then enable a Faradaic current via either a reaction resulting from the particle's intrinsic electrochemical properties or via a catalytic reaction.…”
Section: Introductionmentioning
confidence: 99%
“…The interested reader can consult the references for a discussion on each of the techniques used to observe stochastic events electrochemically: blocking (9, 13), electrocatalytic amplification (1), open circuit potential (16), droplet blocking/reactor (13,14), and ECL (15,17,18). The simplest and most reproducible method of observing collisions is a technique termed blocking, which is so named because particles, which are brought to the electrode by a diffusion-limited flux and/or electrophoretic migration, irreversibly adsorb (1) to the electrode surface, blocking the flux of redox active species.…”
mentioning
confidence: 99%